Changes for Josefina : a winter story - Tripp, Valerie, 1951- (American girls collection., 1998)
When Tía Dolores, the beloved aunt who has cared for the Montoya family since the death of their mother, announces that she is planning to leave, Josefina and her sisters try to find a way to change her mind.